Study the Effect of Manganese Ion Doping on the Size- Strain of SnO2 nanoparticles Using X-Ray Diffraction Data - M. Al-Saadi, Tagreed; A. Kamil, Zahraa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this study, SnO2 nanoparticles were prepared from cost-low tin chloride (SnCl2.2H2O) and ethanol by adding ammonia solution by the sol-gel method, which is one of the lowest-cost and simplest techniques. The SnO2 nanoparticles were dried in a drying oven at a temperature of 70°C for 7 hours. After that, it burned in an oven at a temperature of 200°C for 24 hours. The structure, material, morphological, and optical properties of the synthesized SnO2 in nanoparticle sizes are studied utilizing X-ray diffraction. The Scherrer expression was used to compute nanoparticle sizes according to X-ray diffraction, and the results needed to be scrutinized more closely. The micro-strain indicates the broadening of diffraction peaks for nanoparticles that are not ideal crystals. The extra broadening of the diffraction peak may lead to a miscalculation of the nanoparticle size. We use the Williamson-Hall method to directly compute and discuss the particle size and micro-strain of SnO2 nanoparticles and compare them with results obtained using the Scherrer method. In conclusion, the straight line has been derived due to Williamson–Hall methods demonstrating the nanoparticles' uniformity.